Choroidal neovascularization after intraocular foreign body - Fernández-López, Ester (Dove Medical Press, 2014)
We report an unusual case of choroidal neovascularization secondary to intraocular foreign body (IOFB) penetrating trauma. A 44-year-old man was referred to our department for IOFB trauma in the right eye. Vitrectomy and IOFB extraction was performed with good visual results. However, 2 months after surgery, he returned complaining of a drop in visual acuity. Choroidal neovascularization originating from a direct choroidal rupture at the IOFB impact site was observed. The patient was treated with 6-monthly intravitreal injections of antivascular endothelial growth factor, and showed regression of neovascularization and a final visual acuity of 20/80. IOFB trauma is a serious condition, indeed in spite of initially good results after a favorable surgical outcome. Choroidal neovascularization after direct traumatic choroidal rupture is usually aggressive and requires more active antivascular endothelial growth factor therapy.